Global Issues and Financing for Achieving Sustainable Development Goals - Dr. U. Sarangi (Research Parks Publishers, 2021)
The research paper entitled „Global Issues and Financing for Achieving Sustainable Development Goals’ is a unique research effort to analyze the current frontline global issues that is affecting the global economies at large. In these days of current global crisis, the COVID-19 global pandemic has emerged as not only a global health crisis but also a global humanitarian crisis. The research has made an attempt to study and analyze the cross cutting global issues including the present global pandemic which has taken a serious toll on humanity, but has also affected the various sectors of the global economies such as health, humanitarian, economic, social, geopolitical, environment etc., and other related cross-cutting issues which are vital determinants and key indicators in achieving the Sustainable Development Goals(SDGs). The paper also dwells into the aspect of global financing issues keeping in mind and including finding ways and means for containment of the present global health pandemic by looking into the various aspects of financing needs of the economies to enable these economies to come out such serious economic shocks that has resulted and affected these economies due to the severe outbreak of COVID-19. The research paper also covers and studies other aspects of the global economies such as the Addis Ababa Action Agenda(AAAA) on cross cutting initiatives to develop and built-in synergies for achieving the SDGs, monitoring by the Inter-Agency Task Force on Sustainable Development and the Financing for Global Sustainable Forum(FfSD), upcoming events planned by FfSD, Global issues for FfSD Forum, ECOSOC and its role on International Cooperation in Tax Matters,